Phenotypic characterization and colistin susceptibilities of carbapenem-resistant of Pseudomonas aeruginosa and Acinetobacter spp. - Mohanty, Srujana; Maurya, Vijeta; Gaind, Rajni; Deb, Monorama (The Journal of Infection in Developing Countries, 2013)
Introduction: Pseudomonas aeruginosa and Acinetobcter spp. are important nosocomial pathogens and carbapenem resistance is an emerging threat. Therapeutic options for infections with these isolates include colistin. This study was conducted to determine the prevalence of carbapenem resistance in P. aeruginosa and Acinetobacter spp. bloodstream isolates, phenotypically characterize the resistance mechanisms and evaluate the invitro activity of colistin. Methodology: Consecutive 145 (95 P.aeruginosa and 50 Acinetobacter spp.) non-repeat isolates were included. Antibiotic susceptibility testing was performed per CLSI guidelines. MIC for carbapenems and colistin was performed using Etest. Isolates showing reduced susceptibility or resistance to the carbapenems were tested for metallo-β-lactamase (MBL) production using imipenem-EDTA combined disk and MBL Etest. Results: Carbapenem resistance was observed in 40% P. aeruginosa and 66.0% Acinetobacter spp. Carbapenem-resistant (CA-R) isolates were significantly (p< 0.05) more frequently resistant to the other antibiotics than carbapenem-susceptible isolates. Approximately half of the CA-R strains were multidrug-resistant, and 3.1-5.5% were resistant to all antibiotics tested. MBL was found in 76.3% and 69.7% of the P. aeruginosa and Acinetobacter spp., respectively. Colistin resistance was observed in three (6.0%) Acinetobacter isolates and eight (8.4%) P. aeruginosa. MIC50 for carbapenems were two to four times higher for MBL-positive compared to MBL-negative isolates, but no difference was seen in MIC for colistin. Conclusion: Carbapenem resistance was observed to be mediated by MBL in a considerable number of isolates. Colistin is an alternative for infections caused by CA-R isolates; however, MIC testing should be performed whenever clinical use of colistin is considered.